2020
DOI: 10.15252/msb.20209438
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic enhancers through spatial integration of single‐cell transcriptomics and epigenomics

Abstract: Single-cell technologies allow measuring chromatin accessibility and gene expression in each cell, but jointly utilizing both layers to map bona fide gene regulatory networks and enhancers remains challenging. Here, we generate independent single-cell RNA-seq and singlecell ATAC-seq atlases of the Drosophila eye-antennal disc and spatially integrate the data into a virtual latent space that mimics the organization of the 2D tissue using ScoMAP (Single-Cell Omics Mapping into spatial Axes using Pseudotime order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 126 publications
(216 reference statements)
3
79
1
Order By: Relevance
“…Comprehensive mutagenesis and competition assays revealed three Pros conserved binding sites within these fragments (Supplementary Figure S4), one of them partially overlapping the low-affinity binding site of D-Pax2/Sv (Figure 5B). Interestingly, none of these identified binding sites resemble the known binding sites for Pros identified by SELEX (Hassan et al, 1997), by functional studies (Cook et al, 2003), or by single-cell omics analyses (Bravo González-Blas et al, 2020).…”
Section: Resultsmentioning
confidence: 92%
“…Comprehensive mutagenesis and competition assays revealed three Pros conserved binding sites within these fragments (Supplementary Figure S4), one of them partially overlapping the low-affinity binding site of D-Pax2/Sv (Figure 5B). Interestingly, none of these identified binding sites resemble the known binding sites for Pros identified by SELEX (Hassan et al, 1997), by functional studies (Cook et al, 2003), or by single-cell omics analyses (Bravo González-Blas et al, 2020).…”
Section: Resultsmentioning
confidence: 92%
“…However, the accuracy can be sub-par due to the lack of reference map, and a set of a priori marker genes with known expression patterns is desirable. In Drosophila, ScoMAP (Single-Cell Omics Mapping into spatial Axes using Pseudotime ordering) is another reference-free technique that spatially integrates expression data into a virtual latent space, resembling the organization of a 2D tissue 70 . At the single-cell resolution level, the CSOmap (Cellular Spatial Organization mapper) algorithm can partially reconstruct the tissue spatial organisation based on ligand-receptor interaction 71 .…”
Section: Computational Approaches For Resolving Spatial Gene Expressionmentioning
confidence: 99%
“…In their recent study, González‐Blas et al () integrate single‐cell transcriptomics and epigenomics data and deduce genome‐wide precise enhancer‐to‐gene relationships in single cells of a tissue. Their work closes an important gap in the transcriptional regulation field, and their multi‐dimensional approach (Fig ) was key for achieving this.…”
Section: A Roadmap To Single‐cell Regulatory Genomicsmentioning
confidence: 99%
“…Using random forest regression models, enhancer‐to‐gene relationships were calculated in each cell, which revealed that gene regulation is highly redundant and each gene is controlled by multiple enhancers. The single‐cell information was finally used to deconvolute cell‐type specific effects of bulk derived chromatin accessibility data, which identified new motifs and TF s active in specific cell types of the eye‐imaginal disc (Several elements shown in this Figure have been reused from González‐Blas et al , , including the virtual enhancer activity map, the confocal image showing the enhancer activity in the eye‐antennal disc and the example of the chromatin accessibility QTL , Topic 24).…”
Section: A Roadmap To Single‐cell Regulatory Genomicsmentioning
confidence: 99%